Understanding and responding to family violence risks to children: Evidence-based risk assessment for children and the importance of gender. Issue 1 (March 2019) - Fitz-Gibbon, Kate; Maher, JaneMaree; McCulloch, Jude; Segrave, Marie
This article responds to recent calls to better understand and respond to family violence risks to children. Drawing on the findings of a wider research project on family violence risk which engaged with over 1000 members of Victoria's family violence system through a survey, focus groups and in-depth interviews, this article examines practitioners' views on current practices and future needs for reform to improve family violence risk assessment practices for children. The findings have implications both nationally and internationally, given the dearth of evidence-based family violence risks assessment tools. Key findings reinforce the importance of interagency collaboration and a shared responsibility for children impacted by family violence across services and the importance of specialised training in this area. Caution, however, is raised about ongoing patterns of blame for mothers affected by family violence: we conclude that the need to address children's risk in family violence is critical but ongoing attention to how gendered patterns structure family violence and social responses is also essential.